ANALISIS FAKTA CERITA DALAM FOLKLOR LISAN: CERITA RAKYAT SUNDA SEBAGAI PEMBELAJARAN SASTRA DI SEKOLAH DASAR - S. N. M. Aljamaliah; D. M. Darmadi (Universitas Sebelas Maret, 2023)
Folklore is one of the sastra literature that can be used as teaching materials to help students recognize local wisdom. Sastra Literature can also function as a medium of learning and entertainment to foster emotions in students. Oral literature is literature that includes expressions of the citizens of a culture caused and passed down by oral literature (by word of mouth). As part of culture, oral literature cannot be separated from the influence of values that live and develop in society. These positive values can shape children's character and can foster a love for regional culture. Oral literature can also introduce the culture of the archipelago to students. This study seeks to contribute to literary learning in elementary schools, in this case oral folklore in Sundanese folklore can be used as a source of literary learning material so that folklore can be used as an alternative source of teaching materials by teachers during the learning process. The facts of the story contained in the oral folklore of Sundanese folklore are; plot, characterizations, and setting.